Female reproductive traits of a commercially exploited skate: Atlantoraja platana (Günther, 1880) (Chondrichthyes, Rajidae). Ovarian morphology, gametogenesis and microscopic verification of maturity criteria - Moya, Ana Carolina (2017)
Atlantoraja platana is an endemic species of the Southwest Atlantic Ocean, and is one of the most captured by the local bottom trawl industrial fisheries. In this work, the microscopic architecture of mature female's gonads and the dynamics of follicle development are studied as a contribution to raise awareness of reproductive biology of the species. Folliculogenesis depicts the same histologic pattern as in other Elasmobranchs. Follicles in different degrees of maturation coexist in mature animals. The oogonia were only found in immature individuals. Likewise, atretic follicles were recorded in ovaries of all sexual maturity stages. The microscopic size recorded from the beginning of yolk input is smallest than the detected with the necked eye. This study provides valuable information about female's gametogenesis that could be taken into account in the development of fisheries management.